EFEKTIVITAS METODE ‘IBRAH MAU’IZHAH DALAM MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK di MTS PLUS DARUL HUFADZ JATINANGOR - Maknun, Lulu; Supriadi, Udin; Firmansyah, Mokh. Iman (Universitas Pendidikan Indonesia, 2017)
This present study is conducted based on the ineffectiveness of learning method and model on Akidah Akhlak subject in class VIII. This study aims at identifying the effectiveness of 'Ibrah Mau'i'ah method in STAD learning model on Akidah Akhlak subject in an attempt to improve learning achievements. The method employed in this present study was quasi-experimental method of non-equivalent control group design type using quantitative approach and the instruments were in the form of a written multiple choice in which the results of this test were analyzed using a descriptive statistic approach. The results of this study showed that 'Ibrah Mau'iẓah method in the STAD learning model was assumed to be effective in improving students’ learning achievement. As suggestion for the further studies, it is necessary to carry out a comparative study using other models and a further study in relation to morals.Penelitian ini dilatarbelakangi belum optimalnya metode dan model pembelajaran pada mata pelajaran Akidah Akhlak kelas VIII. Tujuan dari penelitian ini untuk mengetahui efektivitas metode ‘ibrah mauizhah dalam model pembelajaran STAD untuk meningkatkan prestasi belajar. Melalui metode quasi eksperimen jenis nonequivalent control group design dengan pendekatan kuantitatif serta instrumen bentuk tertulis pilihan ganda yang hasilnya dianalisis secara deskriptif statistik, penelitian menunjukkan metode ‘ibrah mauizhah dalam model pembelajaran STAD efektif dalam meningkatkan prestasi belajar siswa. Rekomendasi dari penelitian ini diperlukan penelitian perbandingan dengan model lain serta penelitian lanjutan kaitannya dengan akhlak. Kata Kunci: Metode Ibrah Mauizhah, Model STAD, Prestasi Belajar Akidah Akhlak.